Meta-analysis of the risk of small bowel obstruction following open or laparoscopic colorectal surgery. Issue 5 (22nd February 2016) - Yamada, T; Okabayashi, K; Hasegawa, H; Tsuruta, M; Yoo, J-H; Seishima, R; Kitagawa, Y
Abstract: Background: One of the potential advantages of laparoscopic compared with open colorectal surgery is a reduction in postoperative bowel obstruction events. Early reports support this proposal, but accumulated evidence is lacking. Methods: A systematic review and meta-analysis was performed of randomized clinical trials and observational studies by searching the PubMed and Cochrane Library databases from 1990 to August 2015. The primary outcomes were early and late postoperative bowel obstruction following laparoscopic and open colorectal surgery. Both ileus and bowel obstruction were defined as a postoperative bowel obstruction. Subgroup and sensitivity analyses were performed, and a random-effects model was used to account for the heterogeneity among the studies. Results: Twenty-four randomized clinical trials and 88 observational studies were included in the meta-analysis; 106 studies reported early outcome and 12 late outcome. Collectively, these studies reported on the outcomes of 148 392 patients, of whom 58 133 had laparoscopic surgery and 90 259 open surgery. Compared with open surgery, laparoscopic surgery was associated with reduced rates of early (odds ratio 0·62, 95 per cent c.i. 0·54 to 0·72; P < 0·001) and late (odds ratio 0·61, 0·41 to 0·92; P = 0·019) postoperative bowel obstruction. Weighted mean values for early postoperative bowel obstruction were 8 (95 per cent c.i. 6 to 10) and 5 (3 to 7) per cent for open and laparoscopic surgery respectively, and for late bowel obstruction were 4 (2 to 6) and 3 (1 to 5) per cent respectively. Conclusion: The reduction in postoperative bowel obstruction demonstrates an advantage of laparoscopic surgery in patients with colorectal disease. Abstract : Minimal access lowers risk